Biochar Application in Soils Mitigate Climate Change through Carbon Sequestration - Rakshit, Rajiv; Patra, Ashok K.; Das, Anupam; Das, Debarup (International Journal of Bio-resource and Stress Management, 2023)
There is a large imbalance between carbon release to the atmosphere and carbon uptake by other compartments which leads to a continued increase in atmospheric CO2. Production of biochar formed by pyrolysis of biomass and its storage in soils has been suggested as a means of abating climate change by sequestering carbon. Biochar technology can be a novel approach to retain carbon in a stable form that can be stored outside of the atmosphere for longer time periods. The principal mechanisms operating in soils through which biochar entering the soil is stabilized and significantly increase its life cycle in soil are its particulate nature, recalcitrance, mean residence time and interaction with mineral surfaces.